Phase separation in lithium intercalated anatase: A theory - Velychko, O.V.; Stasyuk, I.V. (Condensed Matter Physics, 2009)
Lithium intercalated anatase used in Li-ion batteries has some special features: coexistence of Li-rich and Lipoor
phases as well as two possible positions for Li ions in the oxygen tetrahedron. A theoretical description
of the compound considering those peculiarities is presented. As shown by the performed symmetry analysis,
the intercalation induced lattice deformation can be accompanied by the ordering of antiferroelectric type
(internal piezoeffect). In the following step, a qualitative illustration of the phase separation in the lithiated
anatase is given within the Landau expansion at the proper choice of coefficients. A microscopic model for
description of the compound is also proposed which combines features of the Mitsui and Blume-Emery-Griffits
models and utilizes the symmetry analysis results. Various ground state and temperature-dependent phase
diagrams of the model are studied to nd a set of model parameters corresponding to the lithiated anatase.
A phase separation into the empty and half-filled phases in a wide temperature range has been found closely
resembling the phase coexistence in the intercalated crystal. In the framework of the model, the two-position
Li subsystem could have the ordering of ferro- or antiferroelectric types which, however, has not been yet
observed by the experiment. Для iнтеркальованого лiтiєм анатазу, що використовується у лiтiй-iонних батереях, характернi спiвiснування багатої та бiдної на лiтiй фаз та наявнiсть двох можливих позицiй для лiтiю у кисневих октаедрах. Запропоновано теоретичний опис цiєї сполуки, що враховує згаданi особливостi. Як показав проведений симетрiйний аналiз, викликана iнтеркаляцiєю деформацiя гратки може супроводжуватися впорядкуванням антисегнетоелектричного типу (внутрiшнiй п’єзоефект). Це дало можливiсть отримати якiсну iлюстрацiю фазового розшарування у лiтiйованому анатазi за допомогою розкладу Ландау з вiдповiдним вибором коефiцiєнтiв. Для опису даної сполуки запропоновано також мiкроскопiчну модель, яка поєднує риси моделей Мiцуї та Блюма-Емерi-Грiффiтса та використовує результати симетрiйного аналiзу. Рiзноманiтнi фазовi дiаграми моделi (як для основного стану, так i температурно-залежнi) дослiджувались з метою встановити набiр модельних параметрiв, що вiдповiдає лiтiйованому анатазу. В широкому температурному дiапазонi виявлено фазове розшарування на порожню та напiвзаповнену фази, що цiлком вiдповiдає спiвiснуванню фаз у iнтеркальованому кристалi. В рамках моделi двопозицiйна пiдсистема лiтiю може мати впорядкування сегнето- чи антисегнетоелектричного типу, яке, однак, наразi експериментально не спостерiгалося.